3(c+4)=-5(c+5)

Simple and best practice solution for 3(c+4)=-5(c+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(c+4)=-5(c+5) equation:



3(c+4)=-5(c+5)
We move all terms to the left:
3(c+4)-(-5(c+5))=0
We multiply parentheses
3c-(-5(c+5))+12=0
We calculate terms in parentheses: -(-5(c+5)), so:
-5(c+5)
We multiply parentheses
-5c-25
Back to the equation:
-(-5c-25)
We get rid of parentheses
3c+5c+25+12=0
We add all the numbers together, and all the variables
8c+37=0
We move all terms containing c to the left, all other terms to the right
8c=-37
c=-37/8
c=-4+5/8

See similar equations:

| A(n)=3n+2. | | 9=(2+3x) | | 4xx2x=60 | | 10+2x-4=18 | | z/4+4=7 | | 4x-10=20+3x | | x=(-4x)-12 | | -5(2x-7)=2(x-15)-7 | | 8w+5=2(2w+1) | | 2(n+9)=24 | | Y=3x2-75 | | 3*(4x-8)=-2*(6-4x) | | (x-5)(40-x)=4×x | | 4y-7+y+11=180 | | 3•(4x-8)=2•(6-4x) | | 11+3x=2(-x+8)-20 | | n+(-3)=10 | | x+8=- | | 3x–2.6=x+8.21 | | 28=9n-8 | | 2n-4=22 | | 0.75x=1.25x+4 | | 23+n=10 | | -28x-30=x-436 | | Y=3x2+-75 | | g+107=-9g-23 | | 2(x-7)=52 | | a-960=-28a-3 | | -3n+75=n+187 | | 16c+8=c-727 | | 1/4x-6=17 | | b+3=-2b-3 |

Equations solver categories